Design and fabrication test jig for cervical bone - Perabu, Moorty (2009)
This thesis deals with the development of cervical bone test jig. The objectives of this thesis are to design the test jig for cervical bone, fabricate the parts and assemble the parts together to complete the cervical bone test jig. The thesis describes the methods of designing and fabricating the mechanical part of the gate system. There the many steps taken to design and fabricate the mechanical part of the gate system. The structural three-dimensional solid modelling of test jig was developed by usingthe SolidWorks engineering drawing software. The fabrication process also undergoes many steps such as material marking, cutting, drilling, welding and grinding. Other than that, it is explaining the procedure of testing where the cervical bone of cow “bovine” to operate the mechanism of the test jig. The results of testing the jig also discussed in this thesis. Finally, the conclusion about this project and the recommendations for the future plan also attached together with this thesis